Pharmacology : a nursing process approach - Kee, Joyce LeFever; Hayes, Evelyn R.; McCuistion, Linda E. (Elsevier Saunder, 2012)
With its concise, straightforward approach, this text puts nursing pharmacology concepts and essential drug calculation skills into a contemporary nursing context to prepare you for real-world drug administration responsibilities. Revised and updated with the most current information-including Prototype Drug Charts, detailed Nursing Process summaries, and NCLEX Study Questions-this 7th edition makes pharmacology more understandable than ever.